The effect of temperature on the microwave aquametry in hevea rubber latex. - Khalid , Kaida (1989)
Theoretical and experimental investigations have been made to determine the effect of temperature (in the range of 27°C - 55°C) on the accuracy of moisture measurement in hevea rubber latex. The measurements are based on the microwave attenuation, operating at 9.5 GHz. The results show that microwave attenuation is affected by temperature and variation of temperature of a few degrees in the latex may introduce inaccuracies of more than 5% in water content measurements.